Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas - Poorani, J. (Pensoft Publishers, 2014)
Abstract. Platynaspis flavoguttata (Gorham) (Coleoptera: Coccinellidae) is redescribed and the male genitalia are illustrated for the first time. It is also recorded from Sri Lanka for the first time. Platynaspis bimaculata (Hoang, 1983) is a new junior synonym of Platynaspis bimaculata Pang & Mao, 1979 (new synonym). Platynaspis kapuri Chakraborty & Biswas, 2000, the replacement name for Platynaspis bimaculata Pang & Mao, 1979 established by Ukrainsky (2007), is also the new replacement name for Platynaspis bimaculata (Hoang, 1983), as both are junior homonyms of Platynaspis bimaculata Weise, 1888 besides being synonyms. Platynaspis hoangi Ukrainsky (2007) is an unnecessary replacement name for Platynaspis bimaculata (Hoang).